IPK-UNGGUL (INOVASI PELAYANAN KAMPUS-UNGGUL); PERWUJUDAN SERVICE EXCELLENCE MENUJU KAMPUS UNGGUL - Page, Muhammad Taufik; Habibi (Stikes Yarsi Mataram, 2026)
Aducational Staff (tendik) play a vital role in service delivery at the faculty and study program levels within a university, as they serve as the backbone of administrative processes directed toward both internal stakeholders (students, lecturers, administrative staff, and other personnel) and external parties (individuals, institutions, communities, and others). The limited availability of training or capacity-building programs on service excellence for administrative staff has resulted in the persistence of attitudes and service behaviors that do not meet expected standards. The aim of this program is to enhance the understanding of Service Excellence among service providers, particularly administrative staff, in order to improve the satisfaction of all campus service users. The program consisted of two components: training sessions and practical field-based improvements. The results demonstrate an increase in knowledge (pre-test: 80% categorized as good; post-test: 100% categorized as good) and improved skills among the administrative staff of the Faculty of Health Sciences, University of West Sulawesi, regarding Service Excellence. In conclusion, this program improved the knowledge and skills of administrative staff, indicating that the quality of services provided to users can be elevated to an excellent level.